Cowpea Mosaic Virus Nanoparticle Enhancement of Hypofractionated Radiation in a B16 Murine Melanoma Model - Duval, Kayla E. A.; Wagner, Robert J.; Beiss, Veronique; Fiering, Steven N.; Steinmetz, Nicole F.; Hoopes, P. Jack (Frontiers in Oncology, 2020)
Introduction: Virus and virus-like nanoparticles (VNPs) have been used for a variety of preclinical treatments, including in situ anti-cancer vaccination. The Cowpea mosaic virus (CPMV) is a VNP that has shown the ability to stimulate an anti-cancer immune response. The goal of this study was to determine if intratumoral CPMV could enhance the immunogenetic and cytotoxic response of hypofractionated radiation (15 Gy or 3 x 8 Gy) in the murine B16 flank melanoma model. Methods: CPMV nanoparticles were delivered intratumorally, 100 μg/tumor to B16 murine melanoma flank tumors alone, and in combination with either 15 Gy or 3 x 8 Gy (3 consecutive days). Tumors were assessed for immune and cytotoxic gene and protein expression, and cytotoxic T cell infiltration 96 hours post treatment. Treatment based tumor control was assessed by a 3-fold tumor growth assay. Results: Both CPMV and radiation alone demonstrated the activation of a number of important immune and cytotoxic genes including natural killer cell and T cell mediated cytotoxicity pathways. However, the combination treatment activated greater expression than either treatment alone. CPMV combined with a single dose of 15 Gy demonstrated greater immune and cytotoxic gene expression, protein expression, CD8+ T cell infiltration activity, and greater tumor growth delay compared to 3 x 8 Gy with CPMV. Conclusion: CPMV presents a unique and promising hypofractionated radiation adjuvant that leads to increased anti-tumor cytotoxic and immune signaling, especially with respect to the immune mediated cytotoxicity, immune signaling, and toll-like receptor signaling pathways. This improvement was greater with a single dose than with a fractionated dose.